ENGLISH VERSION:PHENOTYPIC PORTRAIT OF ESSENTIAL HYPERTENSION AS A TOOL TO INCREASE THE EFFICIENCY OF ITS DIAGNOSIS AND PROGRESSION IN MEN WITH POLYMORPHIC VARIANTS OF THE CARDIOTROPHIN-1 GENE - M.O. Matokhniuk; I.P. Pashkova; V. M. Zhebel (Проблеми екології та медицини)
Chronic heart failure (CHF) is one of the prognostic complications of essential hypertension (EH), which is the most common non-communicable disease in the world. The aim of the study is to improve the effectiveness of diagnosis of EH progression based on cluster analysis, which is based on anthropometric, laboratory and systemic and intracardiac hemodynamics in men 40-60 years. The study included 50 men with asymptomatic EH aged 50.62 ± 0.73 years and 50 men with EH complicated by CHF aged 51.86 ± 0.81 years. All participants underwent standard cardio-graphic examinations, the plasma concentration of cardiotrophin-1 (CT-1) in the blood was determined by enzyme-linked immunosorbent assay (ELISA) and rs8046707 of the CT-1 gene in venous blood samples using the PLR method. The phenotypic portrait of the patient was distinguished by cluster analysis.